Membumikan Moderasi Beragama Melalui Penguatan Literasi Keagamaan di Majelis Taklim di Kelurahan Ujung Kabupaten Soppeng - Sulaeman, Sulaeman; Wahyuni, Sri; Hasriadi, Hasriadi; Wafiyah, Ummul; Muhsin, Muhsin; Suwandi, Icsal; Afandi, Afandi; Kardila, Fika; Sari, Nurul Fatika; Qalbi, Nurul; Sukmawati, Ely (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
The phenomenon of diversity at the grassroots level often faces the challenge of rigid and exclusive religious understandings, which, if left unchecked, can fuel intolerance. In Ujung Village, Soppeng Regency, the Majelis Taklim (Islamic study group) is a strategic center for socio-religious interaction, yet the literary reinforcement of religious moderation values ​​has not been optimally implemented in monthly religious study groups. This Community Service (PkM) activity aims to ground the concept of religious moderation by strengthening religious literacy among Majelis Taklim members, thereby fostering an inclusive, tolerant, and balanced understanding of Islam (tawasuth). The method used was Participatory Action Research (PAR), which included socialization, interactive dialogue (halaqah), and literacy mentoring through discussion of religious moderation material. The results of the activity showed a significant increase in participants' understanding of the four pillars of religious moderation: national commitment, tolerance, non-violence, and accommodating local culture. Majelis Taklim members are now able to identify intolerant narratives and respond to them with a more moderate religious perspective. This activity contributes to strengthening the social resilience of the Ujung Village community against the potential for radicalism and establishes the Majelis Taklim as a driving force for interfaith harmony in Soppeng Regency.